Molecular Mechanisms Regulating Temperature Compensation of the Circadian Clock - Narasimamurthy, Rajesh; Virshup, David M. (Frontiers in Neurology, 2017)
An approximately 24 hr biological timekeeping mechanism called the circadian clock is present in virtually all light sensitive organisms from cyanobacteria to humans. The clock system regulates our sleep-wake cycle, feeding-fasting, hormonal secretion, body temperature and many other physiological functions. Signals from the master circadian oscillator entrain peripheral clocks using a variety of neural and hormonal signals. Even centrally controlled internal temperature fluctuations can entrain the peripheral circadian clocks. But, unlike other chemical reactions, the output of the clock system remains nearly constant with fluctuations in ambient temperature, a phenomenon known as temperature compensation. In this brief review, we focus on recent advances in our understanding of the post-translational modifications, especially a phosphoswitch mechanism controlling the stability of PER2 and its implications for the regulation of temperature compensation.